Tie-in Sale. Tied Up with a Package - Dow Chemical Company (1964)
Color print advertisement for Metalam, a film-and-foil packaging combination manufactured and sold by the Flexible Packaging Sales division of the Dow Chemical Company. The advertisement features chunks of raw beef and McCormick Beef Stew Seasoning packaged in Metalam, with accompanying text detailing the packaging's ability to attract consumers and encourage purchase of tie-in items.
Keywords: Dow Chemical Company; Advertising; Advertising, Industrial; Chemical industry; Corporations; Food--Packaging; Packaging; Plastics in packaging